PENGARUH GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS TENAGA KERJA PROVINSI LAMPUNG - Isabella, Astrid Aprica; Sari, Nety Kumala; Fariza, Dien Nora (Jurnal EBI, 2024)
This study aims to determine the influence of leadership style, work environment, on employee performance at the Lampung Provincial Manpower Office. The research method used is the Quantitative Method with a Comparative Causal research approach with a questionnaire data collection technique with a Likert scale. The population in this study is 182 employees using the Purposive Sampling Technique. The Purposive sampling technique is a sample selection that is carried out based on special characteristics or attributes that are considered to have a significant relationship with previously known characteristics or attributes of the population.The results of the study show that leadership style, work environment, simultaneously affect employee performance. This is shown by the value of Fcal Ftabel (66.255 3.14) and the significant value is less than 0.05, namely (0.000 0.05). And the Adjusted R Square is 0.671, meaning that the contribution of leadership style, work environment, is 67.1%. While the difference (100-67.1% = 32.9%) is explained by other factors or variables that are not used in this study.Keywords: Leadership Style, Work Environment, Performance, Lampung Province